Family integrated care: very preterm neurodevelopmental outcomes at 18 months. Issue 1 (18th June 2021) - Synnes, Anne R; Petrie, Julie; Grunau, Ruth E; Church, Paige; Kelly, Edmond; Moddemann, Diane; Ye, Xiang; Lee, Shoo K; O'Brien, Karel; ,
Abstract : Objective: To examine whether the family integrated care (FICare) programme, a multifaceted approach which enables parents to be engaged as primary caregivers in the neonatal intensive care unit, impacts infant neurodevelopment and growth at 18 months' corrected age. Design/Methods: Prospective cohort study of infants born <29 weeks' gestational age (GA) who participated in the FICare cluster randomised control trial (cRCT) and were assessed in the Canadian Neonatal Follow-Up Network (CNFUN). The primary outcome measure, Cognitive or Language composite score <85 on the Bayley-III, was compared between FICare exposed and routine care children using logistic regression, adjusted for potential confounders and employing generalised estimation equations to account for clustering of infants within sites. Results: Of 756 infants <29 weeks' GA in the FICare cRCT, 505 were enrolled in CNFUN and 455 were assessed (238 FICare, 217 control). Compared with controls, FICare infants had significantly higher incidence of intraventricular haemorrhage (IVH) (19.5% vs 11.7%, p=0.024) and higher proportion of employed mothers (76.6% vs 73.6%, p=0.043). There was no significant difference in the odds of the primary outcome (adjusted OR: 0.92 (0.59 to 1.42) FiCare vs Control) on multivariable analyses adjusted for GA, IVH and maternal employment. However, Bayley-III Motor scores (adjusted difference in mean (95% CI) 3.87 (1.22 to 6.53) and body mass index 0.67 (0.36 to 0.99) were higher in the FICare group. Conclusions: Very preterm infants exposed to FICare had no significant difference in incidence of cognitive or language delay but had better motor development. Trial registration number: Participants in this cohort study were previously enrolled in a registered trial: NCT01852695